2021
DOI: 10.1159/000513213
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Polymyxin B Hemoperfusion on Septic Shock Patients Requiring Noradrenaline: Analysis of a Nationwide Administrative Database in Japan

Abstract: <b><i>Introduction:</i></b> Polymyxin B hemoperfusion (PMX) reduces endotoxin in septic shock patients’ blood and can improve hemodynamics and organ functions. However, its effects on the reduction of septic shock mortality are controversial. <b><i>Methods:</i></b> Using the Japanese diagnosis procedure combination database from April 2016 to March 2019, we identified adult septic shock patients treated with noradrenaline. This study used propensity score matchin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 22 publications
0
17
0
2
Order By: Relevance
“…Conversely, in a study on septic shock with AKI who required CRRT, the 28-day mortality rates with and without PMX were 40.2% and 46.7%, respectively, with a significant improvement with PMX treatment [ 15 ]. Our recent study on noradrenaline-treated septic shock patients showed a substantial improvement of 28-day survival rates by PMX treatment, 77.9% for the PMX group and 71.1% for the non-PMX group [ 16 ]. In addition, our analysis of data from patients with sepsis requiring CHDF showed that PMX significantly improved mortality and shortened hospital and ICU stays [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, in a study on septic shock with AKI who required CRRT, the 28-day mortality rates with and without PMX were 40.2% and 46.7%, respectively, with a significant improvement with PMX treatment [ 15 ]. Our recent study on noradrenaline-treated septic shock patients showed a substantial improvement of 28-day survival rates by PMX treatment, 77.9% for the PMX group and 71.1% for the non-PMX group [ 16 ]. In addition, our analysis of data from patients with sepsis requiring CHDF showed that PMX significantly improved mortality and shortened hospital and ICU stays [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study on the analysis of noradrenaline-administered septic shock patients showed that PMX efficacy is less pronounced in the subgroup of patients with the highest maximum daily dose of noradrenaline [ 16 ]. Furthermore, several reports indicate that PMX treatment is more effective when the time between the onset of shock and the administration of PMX is shorter [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…We also recently used the DPC data to examine the efficacy of PMX in patients with septic shock requiring noradrenaline administration. The data showed that PMX provides significant clinical benefits, including a statistically significant improvement in survival rate and a reduction in ventilator use duration [12]. In the current study, we focused on more severely ill sepsis patients who used CHDF, and we found PMX is useful in this group of patients.…”
Section: Discussionmentioning
confidence: 72%
“…Conversely, in a study on septic shock with AKI who required CRRT, the 28 day-mortality rates with and without PMX were 40.2% and 46.7%, respectively, with a signi cant improvement with PMX treatment [10]. Our recent study on noradrenaline-treated septic shock patients showed a substantial improvement of 28 day-survival rates by PMX treatment, 77.9% for the PMX group and 71.1% for the non-PMX group [11]. In addition, our analysis of data from patients with sepsis requiring CHDF showed that PMX signi cantly improved mortality and shortened hospital and ICU stays [12].…”
Section: Discussionmentioning
confidence: 81%
“…Our previous study on the analysis of noradrenaline-administered septic shock patients showed that PMX e cacy is less pronounced in the subgroup of patients with the highest maximum daily dose of noradrenaline [11]. Furthermore, several reports indicate that PMX treatment is more effective when the time between the onset of shock and the administration of PMX is shorter [16,17].…”
Section: Discussionmentioning
confidence: 99%